Welfare regimes and structures of inequality: a comparative fuzzy set analysis of 23 countries - Pechmann, Philipp (Luxembourg, 2011)
"Welfare states influence the social structure of societies as well as inequalities in various ways. The paper presented here discusses whether specific structures of inequality can be identified in different welfare regimes, i.e. whether specific population groups (elderly, unemployed, single parents and extended families) are affected by inequality in different degrees compared to the total population. Data of the Luxembourg Income Study (LIS) from the years 1990 to 2004 are used to perform a fuzzy-set-analysis for 23 countries. The hypothesis developed in the beginning can only be supported to some extent: A clear relation between welfare regimes and structures of inequality cannot be identified. One reason for this may be the increasing convergence of real-life welfare regimes, which complicates an empirically based discrimination and classification of countries into ideal types as well as an analysis of regime-specific influences on structures of inequality."